Norvegų kalbos lūžio konstrukcija ir jos atitikmenys lietuvių kalboje - Griškevičienė, Aurelija (Baltistica, 2002)
NORWEGIAN CLEFT-SENTENCES AND THEIR EQUIVALENTS INLITHUANIAN The aim of this article is to provide an analysis of Norwegian cleft-sentences and their equivalents in Lithuanian from the Functional Sentence Perspective (FSP). The material for this study has been collected from Lithuanian-Norwegian and Norwegian-Lithuanian translations of fiction. In Scandinavian languages the cleft-construction is an important means of FSP because it helps to arrange the components of FSP correctly for translations from Lithuanian where this construction does not exist. On the other hand the grammatically free word order in Lithuanian gives more possibilities than the fixed word order in Scandinavian languages, where syntactic means for ordering the informational elements in a sentence are limited, and therefore one needs such special constructions as cleft-sentences. The analysis partly confirmed the assumption that cleft-sentences are mostly used in Norwegian translation when the rheme is indicated by inversion or word order which is characteristic for the rheme (the rheme is in sentence final position) in the original. In dialogues the rheme is indicated by stress or emphasis. One can claim that frequently the rheme is indicated by lexical means, but in most cases various components of FSP are combined. Use of cleft-construction in translations from Lithuanian is often an additional way of emphasizing the rheme when the rheme is already expressed by other components of FSP, e. g. lexical means or word order; in questions it is the interrogative word. This article also contains a comparison of the usage of the cleft-construction in translations to Norwegian and Swedish. This led to the conclusion that there are always other ways than cleft-sentences to arrange informational elements correctly in the sentences translated from Lithuanian to Scandinavian languages.